Résister aux inégalités de genres - Geneviève Boivin; Samuel Rhéaume; Julianne Vincent (Communication)
This ethnographic study sheds light on the ways in which a feminist awareness project navigates various complexities and how these relate to and update the processes of ideation and coordination. Using a constitutive approach to communication, particularly ventriloquism (see Cooren, 2010), this research focuses on two figures, that of the mission and the expertise that emerge from the interactions with different team members and thus enable them to be flexible and adapt the project.